(untitled) (Journal of Mathematical Study, 2023)
The aim of this paper is to establish the mapping properties of generalized fractional integral I_ρ and its commutator [b,I_ρ] formed by b∈BMO(R^n) and the I_ρ on generalized fractional weighted Morrey spaces L^p,η,φ_ω (R^n), where φ is a positive and non-decreasing function defined on (0,∞), η∈(0,n) and p∈[1, nη).